Microvillus Inclusion Disease: A Rare Mutation of STX3 in Exon 9 Causing Fatal Congenital Diarrheal Disease - Pournami, Femitha; MK, Alok Kumar; Panackal, Anila V.; Nandakumar, Anand; Prabhakar, Jyothi; Jain, Naveen (Journal of Pediatric Genetics, 2020)
Inherited diarrheal disorders cause serious morbidity resulting in dependence on intensive care and parenteral nutrition. Microvillus inclusion disease (MVID) has been classically described and results from mutations in the gene coding myosin Vb, which is responsible for enterocyte polarization. Newer reports of mutations resulting in truncated syntaxin 3 (STX3) and Munc18-2 (STXBP2) proteins have been elucidated as causative. To date, five cases of STX3 abnormalities resulting in MVID have been described. We report an infant who presented with congenital diarrhea and was determined to have a rare mutation of STX3. This new finding would be beneficial in future functional genotype–phenotype correlation studies.
Keywords: microvillus inclusion disease; congenital diarrheal disease; STX3